A non-isolated pentagon rule C82 cage stabilized by a stretched Sc3N cluster. Issue 34 (29th March 2021) - Guo, Min; Li, Xiaomeng; Yao, Yang-Rong; Zhuang, Jiaxin; Meng, Qingyu; Yan, Yingjing; Liu, Xinye; Chen, Ning
Abstract : A stretched Sc3 N cluster stabilizes a non-IPR C s (39 663)-C82 cage by interacting closely with the adjacent pentagons. Abstract : A novel cluster fullerene, Sc3 N@ C s (39 663)-C82, has been synthesized and characterized. Crystallograpic charaterization unambiguously determines the non-IPR cage structure of C s (39 663)-C82 . Structural analyses further reveal that the Sc3 N cluster is notably stretched to facilitate the interaction with the non-IPR fullerene cage.